ANALYSIS OF METHODOLOGIES FOR NON-DESTRUCTIVE TESTING OF CONCRETE STRUCTURES IN ACCORDANCE WITH EXISTING STATE STANDARDS AND NORMS OF EUROPEAN UNION - D. Yu. Snezhkov; S. N. Leonovich; A. V. Voznishchik (Наука и техника)
Solution of the problem pertaining to increase of the operational period  of buildings and structures is determined mainly by efficiency of control system  for reinforced concrete structures within the whole period of their operation.  The paper contains comparative analysis of  approaches to evaluation of concrete strength in the structures in accordance with the existing norms of the Republic of Belarus and Russia and some European standards, particularly СТБ EN 13791, which have recently become effective. Differences in methodologies  for evaluation of concrete strength characteristics and criteria of concrete compliance with  strength grade have revealed in the paper.